The Influence of Digital Marketing, Management Innovation, and Customer Relationship Management on Customer Loyalty with Customer Trust as a Mediating Variable - Kennis Afriq Febriana Rozana (Utan Kayu Publishing, 2025)
This study analyzes the influence of digital marketing, management innovation, and customer relationship management (CRM) on customer loyalty with customer trust as a mediating variable at Sumbertani Agricultural Store in Sempolan. A quantitative survey design was applied to 180 customers who had made at least two purchases and were aged 18 years or above. Data were collected using a Likert?scale questionnaire and analyzed with Partial Least Squares Structural Equation Modeling (PLS?SEM) using WARPPLS. The results show that digital marketing and management innovation do not have significant direct effects on customer loyalty, while CRM has a strong positive and significant effect. Digital marketing does not significantly influence customer trust, management innovation has a small but significant negative effect, and CRM has a strong positive effect on customer trust. Customer trust significantly affects loyalty and mediates the relationship between CRM and loyalty. The model explains 97.3% of the variance in customer trust and 100% in loyalty, emphasizing the central role of CRM and trust in building long?term loyalty in agricultural retail